ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DI LEMBAGA KURSUS BAHASA INGGRIS IELC SOLO - Muhammad Indra Lestiono, Djumali & Sri Hartono (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of the study was to analyze the effect of service quality simultaneously and partially to consumer loyalty at the English course institute IELC Solo. This research is a descriptive study using quantitative data. This population is the English Language Institute IELC Solo while the sample in this study through the calculation of Slovin formula so that the samples obtained in 85 people. Sampling using purposive sampling technique. The results of this study proved the quality of service positively and positively significant to consumer loyalty at the IELC Solo language institute. Keywords: tangible, reliability, responsiveness, assurance, empathy, loyalty.